Comparative public administration the essential readings - Otenyo, Eric Edwin; Lind, Nancy S., 1958-; Jones, Lawrence (Emerald, 2006)
Public administration scholars and practitioners are increasingly concerned with the need to broaden the field's scope beyond particularistic accounts of administration in given countries. The field of Comparative administration is, therefore, once again thriving. Comparative Administration: The Essential Readings is the first major collection of contributions of major field leaders in this millennium. In this comprehensive and engaging volume, Otenyo and Lind bring together seminal readings in comparative, development public administration and contemporary new public management scholarship. This authoritative and well balanced volume provides readers at all levels with a rare opportunity to contextualize the field's growth and evolution.-In what is truly a remarkable collection of the field's best minds, the book is a rare combination of conceptual and truly comparative empirical works.Without endorsing specific methodologies, the volume is an exciting and succinct overview the field's past and current concerns and interests. An outstanding feature of this book is that it carefully combines both previously published and fresh works considered 'essential' because of their potential impact on the field's development.-The reader will notice that while most of the chapters are broad-brush studies, the selected case-specific chapters are added to illuminate conceptual and theoretical insights.Organized around broad array of topics and themes that include; Methods and Growth of Comparative Public Administration, the Ecology of Administration, Administrative Development, and Development Administration, Planning, Decentralization and Rural Administration, New Public Management, Informatization in administrative settings, and International Administration, the editors seek to provide readers a broader context in which to comprehend public administration in a globalizing world. Hopefully, this timely volume is a valuable resource for a variety of audiences involved in public administration including students and practitioners all over the world.
Keywords: Public administration.; elektronické knihy; electronic books